THE USE OF PROBLEM BASED LEARNING TO IMPROVE STUDENT'S SPEAKING ABILITY - Delta Herliani; Amelia, Amelia (PT. Intelek Cendikiawan Nusantara, 2024)
This study explores the impact of Problem-Based Learning (PBL) on enhancing students' speaking abilities. PBL, an instructional methodology that emphasizes student-centered inquiry and real-world problem solving, is posited to create an engaging and collaborative learning environment. The research involved a diverse group of students subjected to PBL interventions, where they tackled relevant problems requiring verbal communication and presentation. The findings indicate significant improvements in students' speaking skills, including fluency, coherence, and confidence. The study concludes that PBL is an effective strategy for developing speaking abilities, promoting critical thinking, and fostering authentic communication among learners.